Estimation of the mantle conductivity of the southwestern part of the East European Platform - Logvinov, I.; Astapenko, V. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2015)
Geoelectric structure of the mantle at the depth of  100—1000 km is determined through joint interpretation of magnetotelluric sounding in 115 sites in the territory of southwestern part of the East European Platform and geomagnetic induction sounding at geomagnetic  observatories of  Ukraine, Belarus and Poland. Data inversions are considered in terms of conductance distribution. Below the depth of 450 km a sharp increase of conductivity begins. Throughout the whole area a layer of high conductivity can be selected with thickness of about 200 km with the center at a depth of 750 km. A single conductive layer at the depth of 100—200 km, was not revealed as a result of this study. In the vicinity of the Minsk observatory local objects with increased conductivity at different depths in the crust have been marked.